Effect of cyclic load on vertical misfit of prefabricated and cast implant single abutment - Rudys Rodolfo de Jesus Tavarez; Wellington Cardoso Bonachela; Anuar Antônio Xible (University of São Paulo, 2011)
OBJECTIVES: The purpose of this in vitro study was to evaluate misfit alterations at the implant/abutment interface of external and internal connection implant systems when subjected to cyclic loading. MATERIAL AND METHODS: Standard metal crowns were fabricated for 5 groups (n=10) of implant/abutment assemblies: Group 1, external hexagon implant and UCLA cast-on premachined abutment; Group 2, internal hexagon implant and premachined abutment; Group 3, internal octagon implant and prefabricated abutment; Group 4, external hexagon implant and UCLA cast-on premachined abutment; and Group 5, external hexagon implant and Ceraone abutment. For groups 1, 2, 3 and 5, the crowns were cemented on the abutments and in group 4 crowns were screwed directly on the implant. The specimens were subjected to 500,000 cycles at 19.1 Hz of frequency and non-axial load of 133 N in a MTS 810 machine. The vertical misfit (μm) at the implant/abutment interface was evaluated before (B) and after (A) application of the cyclic loading. Data were analyzed statistically by using two-away ANOVA and Tukey's post-hoc test (p<0.05). RESULTS: Before loading values showed no difference among groups 2 (4.33±3.13), 3 (4.79±3.43) and 5 (3.86±4.60); between groups 1 (12.88±6.43) and 4 (9.67±3.08), and among groups 2, 3 and 4. However, groups 1 and 4 were significantly different from groups 2, 3 and 5. After loading values of groups 1 (17.28±8.77) and 4 (17.78±10.99) were significantly different from those of groups 2 (4.83±4.50), 3 (8.07±4.31) and 5 (3.81±4.84). There was a significant increase in misfit values of groups 1, 3 and 4 after cyclic loading, but not for groups 2 and 5. CONCLUSIONS: The cyclic loading and type of implant/abutment connection may develop a role on the vertical misfit at the implant/abutment interface.